2019
DOI: 10.1109/tit.2019.2897772
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Version of Wielandt’s Inequality Revisited

Abstract: Consider a linear space L of complex D-dimensional linear operators, and assume that some power L k of L is the whole set End(C D ). Perez-Garcia, Verstraete, Wolf and Cirac conjectured that the sequence L 1 , L 2 , . . . stablilizes after O(D 2 ) terms; we prove that this happens after O(D 2 log D) terms, improving the previously known bound of O(D 4 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In [39] it is shown that if A is normal then i(A) ≤ (D 2 − d + 1)D 2 . This result has been recently improved [27] to p(T ) ≤ 2D 2 (6 + log 2 (D)). Up to a logarithmic factor, the order O(D 2 log(D)) is optimal just by invoking the optimality of the classical Wielandt inequality.…”
Section: Index Of Injectivity Of a Mpsmentioning
confidence: 92%
“…In [39] it is shown that if A is normal then i(A) ≤ (D 2 − d + 1)D 2 . This result has been recently improved [27] to p(T ) ≤ 2D 2 (6 + log 2 (D)). Up to a logarithmic factor, the order O(D 2 log(D)) is optimal just by invoking the optimality of the classical Wielandt inequality.…”
Section: Index Of Injectivity Of a Mpsmentioning
confidence: 92%
“…For completeness we will give the argument below. In contrast to this border bond dimension 2 representation, the results from [37] on the quantum Wielandt inequality imply that the bond dimension of a translation-invariant restriction has to grow as exp 1 3 ω(3L) , with ω(x) the product logarithm or Lambert function and it has been conjectured that the growth should be of the order L 1/3 [6]. We note however that without the restriction to the translation invariant setting one can also find a bond dimension 2 representation of the W-state.…”
Section: Definition 7 (Bond and Border Bond Dimension)mentioning
confidence: 93%
“…. , A d ) be a d-tuple of D × D-matrices, and assume that there is an N such that the linear span of [4] and is conjectured to be O(D 2 ) [5].…”
mentioning
confidence: 99%
“…The bounds for quantum Wielandt theorem in [8,4,7] were obtained using explicit methods from linear algebra. Our main new insight is the application of nonconstructive Noetherian arguments from nonlinear algebra.…”
mentioning
confidence: 99%
See 1 more Smart Citation